VERBAL AND NON-VERBAL SIGNS IN FACIAL WASH ADVERTISEMENTS: A SEMIOTIC ANALYSIS - Andriani, Ria; Pratiwi, Desak Putu Eka; Santika, I Dewa Ayu Devi Maharani (Yavana Bhasha : Journal of English Language Education, 2021)
This study involves the discovery of verbal and non-verbal signs, which also describe the meaning of verbal and non-verbal signs found in the facial wash commercial advertisements. The data were taken from three printed facial wash advertisements. The data source has been taken from the internet. This study used the semiotic hypothesis provided by Saussure (1983: 65) to find out the verbal and non-verbal signs and the theoretical meaning provided by Barthes (1977) to find out the meaning of verbal and non-verbal signs in the facial wash ads. The analysis used a descriptive qualitative approach to analyze the results. As a result, the three facial wash ads show verbal and nonverbal signs that enable the company to market its product. In the verbal signs of the advertising, most of them contain denotative meaning and non-verbal signs which is in part, contain connotative meaning in certain advertisements. Two advertisements used a female as a model; one advertisement used a male as a model. This means that advertisers seek to gain public attention through the use of pretty females, popular figures and natural extracts or ingredients.